Physical stress tolerance, free radical peroxidation and nitroxidergic system in patients with unstable angina undergoing laser blood radiation - V. V. Belov; U. V. Kharlamova (Кардиоваскулярная терапия и профилактика)
Aim. To investigate low-energy laser radiation (LELR) effects on parameters of nitroxidergic system and free radical peroxidation (FRP), as well as on physical stress tolerability (PST), in patients with unstable angina (UA) and various cardiovascular disease (CVD) status. Material and methods. The study included 100 men with UA (mean age 53±1,0 years). The patients were randomized into two groups, comparable by age, gender, cardiovascular anamnesis, and treatment received. The intervention group (n=49) was administered LELR, the comparison group (n=51) – placebo intervention. The control group included 28 healthy men of the same age. LELR course started at Day 2 after hospitalization, and included 7 sessions. FRP and nitroxidergic system parameters, together with lipid profile, were assessed at Days 2 and 9. PST was assessed in 6-minute walk test (WT) at Day 9 and 3 months later. Results. In UA patients, LELR was associated with significant decrease in atherogenic lipid profile parameters, TBA product level normalization, and increase in nitrite levels. Laser therapy was also associated with significant improvement of PST, regardless of CVD status in anamnesis. Conclusion. Adding laser therapy to complex treatment of UA patients could be recommended as an effective, safe, and UA treatment-optimizing intervention.